Analisis Resepsi Mahasiswa Fakultas Dakwah dan Komunikasi UIN Sunan Ampel pada Citra Perempuan dalam Akun Youtube Opi E-Sports - Hidayat, Mohammad (Dimar Jaya Publishing, 2025)
Digital media, especially YouTube, has now become one of the main channels in shaping public opinion and perception, including in shaping gender representation. OPI E-Sports, as one of the channels that is active in entertainment and online gaming content, often features women in various visual and verbal roles. This study aims to analyze the reception of students at the Faculty of Da'wah and Communication, UIN Sunan Ampel, on the image of women presented on the OPI E-Sports YouTube account. The research method used is qualitative research with a reception analysis approach and Stuart Hall's encoding/decoding theory. The results of the study show that there are three types of receptive reading: dominant-hegemonic, negotiation, and opposition. Some students accept the image of women in a dominant manner in accordance with media constructions, especially those who view the content as a form of ordinary entertainment. However, others show a critical attitude towards gender stereotypes, especially those related to the objectification of women's bodies, passive roles, and unequal representation in the world of e-sports